Pengaruh penambahan glukomanan dari umbi porang terhadap kandungan gizi cookies growol sebagai pangan fungsional untuk obesitas - Puspita Mardika Sari; Desty Ervira Puspaningtyas; Silvia Dewi Styaningrum; Adi Sucipto; Dhea Putri Ananda; Renata Deby Sintia (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Growol (Yogyakarta's traditional fermented cassava) is the potential to be developed as a functional food. Growol cookies was high in dietary fiber content, and low of glychemix index as well as glychemix load score. However, the development of a Growol cookie formula for obesity has never been carried out. The addition of glucomannan from porang tuber was expected as alternative snack for obesity.Objectives: This research aimed to evaluated the effect of inulin and porang glucomannan addition into growol cookies formula with parameter of proximate content (calories, water, ash, protein, fat, carbohydrate) and fiber.Methods: This research was done at Chemix Pratama Laboratory from April to May 2023. It was an observational laboratory study type with simple random design, consists of three (3) formula of growol cookies with formula A (control), B(inulin addition), C (glucomanan porang addition). Proximate analysis consists of thermogravimetri method for water and ash, Kjeldahl for protein, Soxhlet for fat, by difference for carbohydrate, calculative convertion for calories, and gravimetri method for fibe,. Data distribution were analyzed with Shapiro wilk, one way ANOVA continued with LSD for water, ash, protein, fat, carbohydrate and calories datas. Wilcoxon method was using for fiber datas with significant level in 95%.Results: There were not significant differences of calories (p=0,186), water (p= 0,129), fiber (p=0,172) content among three groups. There were significant differences of ash (p<0,001), protein (p=0,030), fat (p=0,012), carbohydrate (0,045) content among groups.Conclusion: Addition of inulin and porang glucomannan were not affected on calories, water, and fiber of growol cookies. However, porang glucomannan addition significantly affected the lowering of ash, fat, protein and carbohydrate content. . Serving size recommendation was 3-4 pieces (± 30 grams). Further study was needed to determine the effectiveness of Growol cookies on obesity management.KeywordsFermented cassava, proximate, obesity